Poli(Disiklo hekzil itakonat -b- propilen oksit) blok kopolimerinin sentezi ve karakterizasyonu - Erdem, Ali Rıza (Fen Bilimleri Enstitüsü, 1996)
Bu çalışmada 6 adet poli(disiklohekzil itakonat-b-propilen oksit) blok kopolimerleri aşamalı yöntemle sentez edilmiştir. Bu amaçla önce, hidroksil son grupları bulunan 1200 ve 2000 molekül ağırlıklı poli(propilen oksit)glikol (PPG-1200 ve PPG-2000) bir alifatik diizosiyanat (izoforon diizosiyanat) üe 80 °C'de kaplama reaksiyonuna sokularak üretanlar, sonra da elde edilen bu üretanların bir hidroperoksit (t-butil hidroperoksit) ve reaksiyonundan bir prepolimer diperkarbamatlar sentez edilmiştir. 2. Aşamada reaksiyon oda sıcaklığında, kuru azot atmosferinde katalizör eşliğinde ve karanlıkta gerçekleştirilmiştir. Elde edilen peroksikarbamatlann molekül ağırlıkları analitik yöntemle belirlenmiştir. Bu reaksiyonlar sonunda elde edilen ve zincir uçlarında peroksit bulunan makrobaşlatıcılar disfldohekzil itakonatın polimerizasyonunda kullanılarak blok kopolimerler çözelti polimerizasyonu yöntemi ile toluende sentez edilmiştir. Bu amaçla önce ticari olarak piyasada bulunmayan disiklohekzil itakonat, itakonik asidin siklohekzil alkol ile sülfürik asit katalizörü eşliğinde esterleşmesi reaksiyonu ile elde edilmiştir. Reaksiyon sıcaklığı 60 °C olarak alındı. Elde edilen kopolimerler saflaştırılarak kurutuldu. İR spektrumları çekilen ara ve son ürünlerin yapılan tanımlanmıştır, örneklerin UV spektrumları ile kopolimerdeki disiklohekzil itakonat yüzdeleri belirlenmiştir. Viskometrik ve GPC yöntemleri ve molekül ağırlıkları tayin edilmiştir. örneklerin termal davranışları DSC ölçümleri ile belirlenmiştir. Homopolidisiklo hekzü itakonatın Tg'si 140 °C olarak bulunmuştur. Blok kopolimerde iki bloka ait Tg'nin ayrı ayrı görülmesi gerektiği halde polipropflen oksit (PPO)'in Tg'si -75 °C olduğundan kopolimerlerin DSC çalışma koşullarında bu bloğun Tg'si gözlenememiştir. Ancak polidisflclohekzil itakonata ait Tg'nin kopolimerdeki PPO yüzdesi arttıkça düştüğü gözlenerek PPO'nun bu kopolimerlere plastifiyan etkisi yapağı belirlenmiştir.

The preparation of linear poh/urethanes composed of soft polyester segments and hard polyurethane sequences was reported 30 years ago. Various oligomers, copolymers, and interpenetrating networks have been prepared by using prepofymers of diols, diisocyanates, hydroperoxides, and azo-compounds containing functional groups. The copolymer synthesis which was carried out in our laboratories is based on the chemical combination of low molecular weight soft poh/ethers with glassy properties of vinyl polymer. In this work, copolymers of dicyclohexyl itaconate (DCHT) and propylene oxide were prepared by using the stepwise procedure. We chose the brittle film- forming PDCHI for the vinyl part of the copolymer, because the data available regarding PDCHI are very limited and DCHI monomer can not be polymerized thermally. The preparation procedure of the copolymers with these stepwise method are given below. The polymeric peroxycarbamates were prepared in two stages. At first stage, the dried hydroxyl-terminated prepolymers (PPG-1200 and PPG-2000) and the aliphatic diisocyanate (IPDI) were reacted at 80 °C bulk under a blanket of dry nitrogen, for 80 h. The molar ratio of diisocyanate to prepolymers were taken to be three in order to prevent undesired chain extension. The resulting products were decantated with dried petroleum ether in order to separate the excess of diisocyanate. The resulting product was dried at 70°C. The isocyanate content of the end-capped products were determined by end group titration of isocyanates and this experimental results were found to be in agreement with the theoretical values. The reaction of this stage is : HO 4- CH - CH2 - O 4- H + 2 OCN - (C1QH1a) - NCO I n CH3 IPDI PPG (n depends on the molecular weight) OCN-(C10H18)-N-C-O 4-CH-CH2-0 4- | II I n/2 H O CH3 OCN -R'- NCO VI In the second step the diisocyanate-terminated urethane was reacted with dried t-butyl hydroperoxide in methylene chloride. A few drops of T-12 catalyst was added to the reaction mixture. The reaction was carried out under a dry nitrogen blanket, at room temrwrature, in the dark, for 200 h. The molar ratio of t-butyl hydroperoxide to urethane was approximately three. The resulting peroxicarbamate were isolated by decantating in petroleum ether and dried in vacuo at room temperature. Their molecular weights were calculated from their peroxide contents and Ibis decantation procedure was repeated until the desired theoretical results were obtained. The molecular weights of peroxycarbamates are shown in Table-L Table I Preparation of Peroxycarbamates * Molecular weight of peroxycarbamates found experimentally. The reaction mechanism of second stage is given as: CH3 I OCN-R'-NCO + 2HOO-C-CH3 - I CH3 CH? hUC-C-OO-C-N-(C10H18)-N-C-O -f CH-CH2-0 -)- II I O H I II H O n/2 CH3 OH H ü CH3 Ri OO - R" - OO - R-, (polymeric peroxycarbamate) ^2 Synthesis of Copolymers The prepared peroxycarbamates were used as initiators for the synthesis of copolymers of dicyclohexyl-itaconate (DCHI). Dicyclohexyl-itaconate were synthesized from the esterification of itaconic acid by cyclohexyl alcohol with sulphuric acid as catalyst vii Weighted amounts of the peroxycarbamates were mixed in predetermined amounts of monomer in the Pyrex tubes. The mixtures were then degassed on a vacuum line (1.33 x 10"2 N/m2). The solutions were distributed in Pyrex tubes immersed in thermostatically controlled baths and polymerization was carried out for 300 h. at 60°C. The solid products were dissolved in toluene and then precipitated in large volumes of methanol. The copolymers were filtered and dried in vacuo at 50°C. Results and Discussion Six copolymers of DCHI were synthesized from the two different molecular weights of peroxycarbamates of polypropylene oxide (PPO). The weight percentage of PPO incorporated into the polymeric product ranged from 16.7 to 40.0 %. As the proportion of PPO incorporated into the polymeric material increases, the overall conversion of DCHI to polymer and the intrinsic viscosities of the final copolymeric products decrease. The characteristics of copolymers are shown in Table-H There is not a great difference in the IR spectra of homopolymers and copolymers, except N-H stretching in the peroxycarbamate around 3440 cm"1. The principal absorption peaks for the homopolymers and copolymers are similar. The FTTR spectra of peroxycarbamate, PDCHI homopolymer and copolymer No. 1 are shown in Figure 1. UV analysis were based on the determination the absorbances of pure PDCHI, of peroxycarbamate and of the copolymers at the wavelength of 229 run. in cyclohexan. Molecular weight of the copolymers were determined by viscometric and gel permeation chromatographic measurements. Intrinsic viscosities were measured at 25 °C in toluene solution and the following relationship for homopolymer of PDCHI was used approximately for copolymers. [rj] = 13. 1 x 1 0"s x Mv° 623 (dL/g) The glass transition temperature of PDCHI homopolymer was found to be 140 °C by DSC measurements. This result is identical to the literature. The Tg values of block copolymers belonging to the Tg of homopolymer were lower than the homopolymer depending on the PPO % in the copolymers. This means that low molecular weight PPO affected the block copolymers as a plasticizer. We could not see the low Tg values of the PPO block (Tg= -75 °C) in the copolymeric samples. Because the DSC measurements were conducted above the room temperature. viii s es H en U 4> S _>» "o o o s o s o es es v- O o o es 6 VO T3 Wi O O o es 3 p- p-( ÖD C '55 3 >».O O- 2 o, 2 P en c es o o, o O v.*< o IX 4000 3000 2000 1500 1000 400 cm,-1 Figure 1: FTIR spectra of (a) Peroxycarbamate, (b) PDCHI homopolymer, (c) Copolymer No. 1
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Kimya; Kopolimerler; Chemistry; Copolymers